2021
DOI: 10.1021/acsami.1c03608
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Interfacial Ion-Transport Kinetics Using Polyelectrolyte Membranes for Additive- and Effluent-free, High-Performance Electrodeposition

Abstract: The development of high-performance, environmentally friendly electrodeposition processes is critical for emerging coating technologies because current technologies use highly complex baths containing metal salts, supporting electrolytes, and various kinds of organic additives, which are problematic from both environmental and cost perspectives. Here, we show that a 200 μm-thin polyelectrolyte membrane sandwiched between electrodes effectively concentrates metal ions through interfacial penetration, which incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Our previous study on setup A demonstrated that at constant voltage electrodeposition, the copper ions penetrated the solid, waterswollen polyelectrolyte membrane from the electrolyte solution, diffused through the membrane via an ion exchange reaction, and were finally reduced on the cathode surface. 26 Theoretical modelling and our experimental results revealed that ion penetration from the electrolyte solution into the polyelectrolyte membrane is the rate-determining step at the applied voltage up to 1.0 V using a 200 μm-thick membrane. 26 During constantvoltage electrodeposition, the current density decreases in the early stage of electrodeposition because of the decrease in the concentration of copper ions in the polyelectrolyte membrane, after which the current density stabilizes when the system reaches the steady state because of the balance between the deposition and penetration rates (Fig.…”
Section: Rsc Applied Interfaces Papermentioning
confidence: 66%
See 4 more Smart Citations
“…Our previous study on setup A demonstrated that at constant voltage electrodeposition, the copper ions penetrated the solid, waterswollen polyelectrolyte membrane from the electrolyte solution, diffused through the membrane via an ion exchange reaction, and were finally reduced on the cathode surface. 26 Theoretical modelling and our experimental results revealed that ion penetration from the electrolyte solution into the polyelectrolyte membrane is the rate-determining step at the applied voltage up to 1.0 V using a 200 μm-thick membrane. 26 During constantvoltage electrodeposition, the current density decreases in the early stage of electrodeposition because of the decrease in the concentration of copper ions in the polyelectrolyte membrane, after which the current density stabilizes when the system reaches the steady state because of the balance between the deposition and penetration rates (Fig.…”
Section: Rsc Applied Interfaces Papermentioning
confidence: 66%
“…26 Theoretical modelling and our experimental results revealed that ion penetration from the electrolyte solution into the polyelectrolyte membrane is the rate-determining step at the applied voltage up to 1.0 V using a 200 μm-thick membrane. 26 During constantvoltage electrodeposition, the current density decreases in the early stage of electrodeposition because of the decrease in the concentration of copper ions in the polyelectrolyte membrane, after which the current density stabilizes when the system reaches the steady state because of the balance between the deposition and penetration rates (Fig. 2).…”
Section: Rsc Applied Interfaces Papermentioning
confidence: 66%
See 3 more Smart Citations